Răspuns:
Fie [tex]f(x)=\sqrt{\ln\left(1+e^x\right)}, \ g(x)=\sqrt{e^x}[/tex] și F și G câte o primitivă a lor. Atunci limita devine
[tex]\displaystyle\lim_{x\to 0}\frac{F(tg x)-F(0)}{G(\sin x)-G(0)}[/tex]
Avem cazul [tex]\displaystyle\frac{0}{0}[/tex] și se aplică l'Hospital
[tex]l=\displaystyle\lim_{x\to 0}\frac{F'(tgx)\cdot\displaystyle\frac{1}{\cos^2 x}}{G'(\sin x)\cos x}=\lim_{x\to 0}\frac{\sqrt{\ln\left(1+e^{tgx}\right)}}{\sqrt{e^{\sin x}}}\cdot\frac{1}{\cos^3x}=\sqrt{\ln 2}[/tex]
Explicație pas cu pas: